The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1186/1475-2875-13-399
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent use of sulphadoxine-pyrimethamine for malaria prevention: a cross-sectional study of knowledge and practices among Ugandan women attending an urban antenatal clinic

Abstract: BackgroundThe WHO recommends supervised administration of sulphadoxine-pyrimethamine (SP) as intermittent preventive treatment for malaria (IPTp) during pregnancy. Logistical constraints have however favoured unsupervised intake of SP-IPTp, casting doubts whether recent guidelines requiring more frequent intake can be effectively implemented. To propose strategies for enhancing compliance under limited supervision, this study sought to identify pregnant women’s knowledge and practices gaps as well as determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…Exit interviews were used to collect data from pregnant women attending ANC at Mulago Hospital. Data for this study was obtained as part of a larger cross-sectional study on malaria, IPTp and anti-malarial drug use among Ugandan women, some of which was recently published [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exit interviews were used to collect data from pregnant women attending ANC at Mulago Hospital. Data for this study was obtained as part of a larger cross-sectional study on malaria, IPTp and anti-malarial drug use among Ugandan women, some of which was recently published [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Where no effort is made to ascertain actual user compliance, such findings remain questionable, especially coming from resource-constrained settings where unsupervised administration of SP is the norm, contrary to guidelines. As argued elsewhere, the presence of such records does not necessarily translate into intake compliance [21, 22]. Our findings are however limited by the small sample sizes used that may not be adequately powered to detect true differences between the groups.…”
Section: Discussionmentioning
confidence: 76%
“…However, such findings in most cases are hampered by the exclusive reliance on self-reports and antenatal records to ascertain SP use. Because unsupervised SP-IPTp administration is a common occurrence in many resource-limited settings, we have previously argued that self-reports and ANC records may not necessarily translate into SP intake compliance [21, 22]. Moreover, where intake was ascertainable, studies have continued to show effectiveness of SP-IPTp [13, 2329].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to one of these studies, good knowledge on the use of SP during pregnancy was significantly predictive of good adherence to IPTp-SP [25]. In 2010, in Nigeria, another study showed that women's comprehensive knowledge of malaria including its prevention during pregnancy through the use of IPTp-SP was associated with good adherence to IPTp-SP [25]. All this confirms that adequate knowledge on IPTp-SP by pregnant women could improve their adherence.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, they identified other factors such as low antenatal coverage and prenatal consultations in the private sector. Thus, according to one of these studies, good knowledge on the use of SP during pregnancy was significantly predictive of good adherence to IPTp-SP [25]. In 2010, in Nigeria, another study showed that women's comprehensive knowledge of malaria including its prevention during pregnancy through the use of IPTp-SP was associated with good adherence to IPTp-SP [25].…”
Section: Discussionmentioning
confidence: 97%